Organized crime in Chicago: beyond the Mafia - Lombardo, Robert M. (University of Illinois Press)
Explaining organized crime -- The gem of the prairie -- The black Mafia -- The syndicate -- The Forty-two Gang -- The outfit -- The outfit as a complex organization -- Street crew neighborhoods